MEDDPOP: una aplicación para PYMES del sector salud basada en ODOO - Naranjo Sánchez, Bertha Alice (2018)
The purpose of this academic article is to demonstrate the main benefits of using an automated system in a medical SME focused on the specialization of otolaryngology using free software and open source technology tools. Using a process optimization approach, the components that allow us to demonstrate the administrative and operational improvement in said SME are developed. It describes the technological architecture used based on the needs of this small and medium business, describes the research methodology used in the survey of information, a survey is applied, amatrix of indicators is created for each activity of the relevant processes. evidencing the improvement obtained qualitatively and quantitatively. The results obtained show a comparative productivity based on the management time of the manual activities carried out by the doctor and the auxiliary using the implemented system where a remarkable advantage is appreciated after the use of this tool, with this it is possible to demonstrate that the TICs allow to automate processes and help in the organizationalimprovement of SMEs.